(untitled) (Research, Society and Development, 2025)
Motor development is influenced by genetic and environmental factors, and primitive reflexes are indicators of neurological development. Early assessment is essential to identify delays, enabling timely interventions that benefit children. This research aimed to evaluate the knowledge of teachers at Municipal Early Childhood Education Centers about children’s motor development in early childhood education. It is a cross-sectional, quantitative study conducted in four CMEIs in Cascavel, Paraná. Data collection was conducted using a semi-structured physical questionnaire; the data obtained were analyzed using frequency distribution and presented in graphs. The sample consisted of 31 teachers. The results indicated that 87% of teachers had an average level of knowledge on the subject, 100% of respondents recognized the importance of integration between health and education professionals, 97% of participants highlighted the importance of specific training in the use of scales to assess motor development, 83% highlighted as extremely important the regular practice of motor assessment of children and the use of specific tools to identify possible delays in motor development, and 16% classified it as very important. 24 teachers carry out activities that promote children’s motor development as an integral part of pedagogical practice. The findings highlight the need for investments in continuing education and technical-pedagogical support for teachers, with a view to expanding knowledge about children’s motor development and strengthening educational practices that promote the integral development of children.children’s motor development and strengthening educational practices that promote children’s comprehensive development.